Changes in Bioactive Compounds of Cherry Laurel Fruit (Prunus Laurocerasus L.) Treated with Modified Atmosphere Packaging and Aloe vera During Shelf Life - Burhan Öztürk (Journal of New Results in Science)
In the study, the changes in vitamin C, total phenolic compounds, total monomeric anthocyanin and antioxidant activity (according to ABTS and FRAP test) of cherry laurel fruits treated with modified atmosphere packaging (MAP) and Aloe vera gel kept in shelf life (21±1 °C and 80±5%) for 3 days after fruit were stored in cold storage (0±0.5 °C and 90±5%), were investigated. In general, bioactive compounds decreased with progressing storage periods. In the last shelf life measurement (60+3 days), vitamin C and total phenolics of fruit with MAP and Aloe vera-treated were significantly higher than the control. When the anthocyanin content was examined, the anthocyanin content of the fruit kept in MAP was found to be significantly higher than the control fruits. In the last three shelf-life measurements, the antioxidant activity of MAP and Aloe vera-treated fruit was measured significantly higher than the control in both ABTS and FRAP tests. As a result, it has been revealed that MAP and Aloe vera can be used as a tool to delay the losses of quality that occurs during the shelf life of cherry laurel fruit.